"We are Still Not Done; We Need to Keep this Organisation Alive". Issue 5 (26th September 2022) - Lorenzo-Arribas, Altea
Abstract: Japanese biostatistician Motomi "Tomi" Mori is chair of the organising committee of the inaugural International Day of Women in Statistics and Data Science on 11 October 2022, and served as the President of the Caucus for Women in Statistics last year. She speaks candidly to Altea Lorenzo-Arribas about her work and the challenges she has faced